PENGARUH INSTITUSI (GOOD GOVERNANCE) TERHADAP KINERJA PERUSAHAAN: STUDI KASUS LPD DI BALI - Wiwin Setyari, Ni Putu (PIRAMIDA, 2012)
This paper analyze institutional and good governance Lembaga Perkreditan Desa (LPD) in Bali. This research want to know are they institutional dan good governance in LPD. The result is institutional LPD have good governance in which they are we can see at management LPD in Bali and have succesfully to help many people include poor people to develop their live and business. Bali governance have big attention and union custom also give positive result about LPD in Bali.
Keywords: institutional; good governance; LPD